27.5k views
2 votes
If p is the hypothesis of a conditional statement and q is the conclusion, which is represented by q-p?

User Andrew Liu
by
4.7k points

2 Answers

4 votes

Answer:

NOT the contrapositive of the original conditional statement

Explanation:

User Shauryachats
by
4.9k points
2 votes

Answer: q ⇒ p represents the CONVERSE of the original conditional statement.

Step-by-step explanation: Given that p is the hypothesis and q is the conclusion of a conditional statement.

We are to find the representation of q ⇒ p.

We know that

if we interchange the hypothesis and conclusion of a conditional statement, then the new statement is the CONVERSE of the original statement.

In the given conditional statement, since p is the hypothesis and q is the conclusion, so

the statement is p ⇒ q.

So, q ⇒ p is formed by interchanging hypothesis and conclusion.

Thus, q ⇒ p represents the CONVERSE of the original conditional statement.

User Yudong Li
by
5.4k points